Voltage-based control of a non-isolated Ćuk converter - Yiong, Chun Sern (2015)
This project aims to design and build controllers to regulate the output voltage of the Ćuk converter. In this report, the circuit designs, implementation and control of a Ćuk converter will be presented. For the first part of the project, voltage mode based controller was used to regulate the output voltage of the converter. As for the second part of the project, sliding mode control was used. The controllers were designed to fulfill their voltage tracking abilities criteria. The controllers will also undergo interference load test to determine their robustness. Experimental results are also presented to verify that these criteria were achieved.